Mouthpiece ventilation in neuromuscular disorders: Narrative review of technical issues important for clinical success. (April 2021) - Toussaint, Michel; Chatwin, Michelle; Gonçalves, Miguel R.; Gonzalez-Bermejo, Jésus; Benditt, Joshua O.; McKim, Doug; Sancho, Jesus; Hov, Brit; Sansone, Valeria; Prigent, Hélène; Carlucci, Annalisa; Wijkstra, Peter; et al.
Abstract: In neuromuscular disorders (NMDs), nocturnal non-invasive ventilation (NIV) via a nasal mask is offered when hypercapnic respiratory failure occurs. With disease progression, nocturnal NIV needs to be extended into the daytime. Mouthpiece ventilation (MPV) is an option for daytime NIV. MPV represents a difficult task for home ventilators due to rapidly changing load conditions resulting from intermittent connections and disconnections from MPV circuit. The 252nd ENMC International Expert Workshop, held March 6th to 8th 2020 in Amsterdam, reported general guidelines for management of daytime MPV in NMDs. This report could not present all the detail regarding the technical issues important for clinical success of MPV. Based on the expert workshop discussions and the evidence from existing studies, the current narrative review aims to identify the technical issues of MPV and offers guidance via a decisional algorithm and educational figures providing relevant information that is important for successful implementation of MPV. Highlights: Mouthpiece ventilation (MPV) represents a difficult task for home ventilators due to rapidly changing load conditions. Circuit leakage is a natural part of MPV. Volume-cycled ventilation copes better with circuit leakage than pressure-cycled ventilation. Volume-cycled ventilation is considered as the first line mode to initiate MPV since it allows intermittent lip sealing without leak compensation. Ventilators equipped with a dedicated MPV mode provide 10 new technological properties which favors the use of MPV at home.